Assessing the Association between Agile Maturity Model Levels and Perceived Project Success - Henriques, Vaughan (Department of Information Systems, 2018)
The underlying philosophy of the agile manifesto is embodied in principle one which promotes the continuous delivery of software that is deemed valuable by the customer, while principle twelve encourages continual improvement of the delivery process. This constant improvement, or maturity, is not a concept unique to agile methods and is commonly referred to as a maturity model. The most common of maturity model is the Capability Maturity Model Integrated (CMMI). However, research consensus indicates CMMI is incompatible with agile implementation, specifically at higher levels of maturity without sacrificing agility. Agile maturity models, which are aligned to agile principles encourage continuous improvement while maintaining agility. Given the underlying philosophy of the agile manifesto, this research hypothesises that an increase in agile maturity is associated with improved perceived project success, by using a conceptual model based on an existing agile maturity model and how each of the maturity levels are related to the perceived project success. The research also brings to light the concept of perceived project success, showing success in an agile environment is a subjective concept. Conducted quantitatively, the findings of this research show which specific focus areas within each of the maturity levels is most strongly correlated with perceived project success and concludes an increasing correlation between the maturity levels and perceived project success.